Jenis-Jenis Burung di Kawasan Cagar Alam Lembah Harau Sumatera Barat - Gita Herliza Sari; - Dahelmi; Wilson Novarino (Jurnal Biologi Universitas Andalas, 2012)
A study on bird species identification at Lembah Harau Nature Reserve, West Sumatra has been conducted from April to May 2012. This study aimed to record bird species by direct observation along road and it’s tributaries. We identified all species and put them into MacKinnon list to predict a total number of species existed in the area. This study found 50 birds species lived in the nature reserve those belong to 24 families and 9 orders. The most abundant was Passeriformes that consist of 36 species and 15 families.Keywords : avifauna, nature reserve, Harau Valley, West Sumatra